Non-toxigenic Corynebacterium ulcerans sequence types 325 and 339 isolated from two dogs with ulcerative lesions in Italy. (May 2018) - Carfora, Virginia; Scarampella, Fabia; Iurescia, Manuela; Donati, Valentina; Stravino, Fiorentino; Lorenzetti, Serena; Menichini, Erika; Franco, Alessia; Caprioli, Andrea; Battisti, Antonio
Corynebacterium ulcerans, an emerging pathogen related to C. diphtheriae and C. pseudotuberculosis, is able to cause disease in both human and animal hosts. C. ulcerans may harbor acquired virulence factors such as dermonecrotic exotoxin phospholipase D (PLD) and the prophage-encoded diphtheria toxin (DT). Infections typically occur in persons reporting close contact with animals. In pets, C. ulcerans has been isolated from both asymptomatic carriers and clinically affected dogs and cats. We describe the isolation and characterization of C. ulcerans strains from 2 pet dogs with ulcerative lesions in Italy. The 2 isolates tested negative for both DT genes, but were PLD-producers and belonged to sequence types (STs) 325 and 339. These 2 cases highlight that C. ulcerans cutaneous infections might be underestimated in pets, given that many veterinary laboratories do not routinely consider and/or identify Corynebacterium species from cutaneous samples. Early detection and molecular typing of C. ulcerans is essential in order to implement effective treatment and to prevent diffusion and possible zoonotic transmission of certain STs.